Fluorescence microscopy for visualizing single-molecule protein dynamics - Yokota, Hiroaki (Biochimica et biophysica acta. General subjects, 2020)
Single-molecule fluorescence imaging (smFI) has evolved into a valuable method used in biophysical and biochemical studies as it can observe the real-time behavior of individual protein molecules, enabling understanding of their detailed dynamic features. smFI is also closely related to other state-of-the-art microscopic methods, optics, and nanomaterials in that smFI and these technologies have developed synergistically. This paper provides an overview of the recently developed single-molecule fluorescence microscopy methods, focusing on critical techniques employed in higher-precision measurements in vitro and fluorescent nanodiamond, an emerging promising fluorophore that will improve single-molecule fluorescence microscopy. smFI will continue to improve regarding the photostability of fluorophores and will develop via combination with other techniques based on nanofabrication, single-molecule manipulation, and so on. Quantitative, high-resolution single-molecule studies will help establish an understanding of protein dynamics and complex biomolecular systems. •Key features of single-molecule fluorescence imaging have been reviewed.•Fluorescence labeling, surface-coating methods, and modern microscopy are described.•Overview is given for frequently used fluorophores, dyes, and quantum dots.•Fluorescent nanodiamond, a promising fluorophore, is introduced.•Improved photostability and other concurrent methods can further develop the method.